Secondary battery, graphite negative electrode material and preparation method of graphite negative electrode material
Through microwave irradiation and graphitization treatment, the problem of high-temperature graphitization treatment causing the collapse of graphite material crystal structure is solved, and efficient preparation of graphite negative electrode materials and the extension of the cycle life of secondary batteries are achieved.
Patent Information
- Application Number
- CN202411999793.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-18
AI Technical Summary
High-temperature graphitization treatment leads to the collapse of the crystal structure of the graphite material, affecting the cycle life of the secondary battery.
Microwave irradiation is used to improve the crystal structure of graphite material, and graphite negative electrode material is formed through pickling, microwave irradiation, water washing and graphitization treatment.
By improving the crystal structure of graphite material, the cycle life of the secondary battery is extended and the electrochemical performance is improved.
Smart Images

Figure CN119841310A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of new energy technology, and in particular, relates to a secondary battery, a graphite negative electrode material and a preparation method thereof. Background Art
[0002] Traditional graphite materials are widely used in lithium-ion batteries.
[0003] Among some related technologies, high-temperature graphitization treatment is an effective method to improve the structural stability and electrochemical properties of graphite materials.
[0004] However, the high-temperature graphitization treatment method has the problem of collapsing the crystal structure of the graphite material, thereby affecting the cycle life of the secondary battery constituted by it. Summary of the invention
[0005] In view of this, the present application provides a secondary battery, a graphite negative electrode material and a preparation method thereof, aiming to solve the aforementioned technical problems.
[0006] In a first aspect, an embodiment of the present application provides a method for preparing a graphite negative electrode material, comprising: subjecting an acid-washed graphite material to microwave irradiation; subjecting the microwave-irradiated graphite material to water washing; and subjecting the water-washed graphite material to graphitization.
[0007] Optionally, in some embodiments of the present application, the raw material of the graphite material is microcrystalline graphite.
[0008] Optionally, in some embodiments of the present application, the mass percentage of the carbon content of the microcrystalline graphite ranges from 80% to 95%.
[0009] Optionally, in some embodiments of the present application, the median particle size of the microcrystalline graphite ranges from 8 μm to 22 μm.
[0010] Optionally, in some embodiments of the present application, the method for preparing the graphite negative electrode material further comprises:
[0011] Coating the graphite material after graphitization to form the graphite negative electrode material;
[0012] And / or, pickling the graphite material, wherein pickling the graphite material comprises:
[0013] Mix concentrated sulfuric acid, ammonium sulfate and graphite material according to a preset ratio;
[0014] A mixture of concentrated sulfuric acid, ammonium sulfate and graphite material is maintained at a preset temperature for a preset period of time.
[0015] Optionally, in some embodiments of the present application, the pickling of the graphite material includes: mixing concentrated sulfuric acid, ammonium sulfate, and the graphite material in a preset ratio; and maintaining the mixture of concentrated sulfuric acid, ammonium sulfate, and the graphite material at a preset temperature for a preset time.
[0016] Optionally, in some embodiments of the present application, the preset temperature ranges from 50°C to 70°C.
[0017] Optionally, in some embodiments of the present application, the preset duration ranges from 1 hour to 3 hours.
[0018] Optionally, in some embodiments of the present application, the mass ratio of the ammonium sulfate to the graphite material is in the range of 1:(0.33-0.5).
[0019] Optionally, in some embodiments of the present application, when the pickled graphite material is subjected to microwave irradiation, the frequency of the microwave irradiation ranges from 1.85 GHz to 3.15 GHz.
[0020] Optionally, in some embodiments of the present application, the duration of microwave irradiation on the acid-washed graphite material ranges from 8 min to 25 min.
[0021] Optionally, in some embodiments of the present application, in a second aspect, embodiments of the present application provide a graphite negative electrode material, which is prepared using the aforementioned graphite negative electrode material preparation method.
[0022] In a third aspect, an embodiment of the present application provides a secondary battery, comprising a negative electrode prepared from the aforementioned graphite negative electrode material.
[0023] Beneficial effects of the present application: Provided are a secondary battery with improved crystal structure through microwave irradiation, a graphite negative electrode material and a preparation method thereof. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without paying any creative work.
[0025] Figure 1 It is a schematic diagram of the main steps of the method for preparing the graphite negative electrode material provided in some embodiments of the present application;
[0026] Figure 2 This is an electron microscope photo of the graphite material at the first magnification before treatment;
[0027] Figure 3 This is an electron microscope photo of the graphite material at the first magnification before treatment;
[0028] Figure 4 This is an electron microscope photograph of the graphite negative electrode material obtained after being processed by the preparation method of the present application at the second magnification;
[0029] Figure 5 This is an electron microscope photograph of the graphite negative electrode material obtained after being processed by the preparation method of the present application at the second magnification;
[0030] Figure 6 This is an electron microscope photograph of the graphite negative electrode material obtained after being processed by the preparation method of the present application at the third magnification. DETAILED DESCRIPTION
[0031] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative work belong to the scope of protection of the present application. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present application, and are not used to limit the present application.
[0032] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0033] In this application, unless otherwise stated, directional words such as "upper" and "lower" generally refer to the upper and lower parts of the device in actual use or working state, specifically the drawing direction in the accompanying drawings; while "inner" and "outer" refer to the outline of the device. In addition, in the description of this application, the term "including" means "including but not limited to". The terms first, second, third, etc. are used only as labels and do not impose numerical requirements or establish an order.
[0034] In this application, "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural.
[0035] In the present application, "at least one" means one or more, and "plurality" means two or more. "One or more", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0036] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0037] Reference Figure 1 As shown, the present application embodiment provides a method for preparing a graphite negative electrode material, which mainly includes the following steps:
[0038] S101: irradiating the pickled graphite material with microwaves;
[0039] S102: washing the graphite material after microwave irradiation;
[0040] S103: graphitizing the washed graphite material;
[0041] S104: coating the graphite material after graphitization to form the graphite negative electrode material.
[0042] In some embodiments of the present application, the raw material of the graphite material is microcrystalline graphite.
[0043] In some embodiments of the present application, the mass percentage of the carbon content of the microcrystalline graphite ranges from 80% to 95%.
[0044] In some embodiments of the present application, the median particle size of the microcrystalline graphite ranges from 8 μm to 22 μm.
[0045] In some embodiments of the present application, the method for preparing the graphite negative electrode material further includes: acid washing the graphite material.
[0046] In some embodiments of the present application, the pickling of the graphite material includes: mixing concentrated sulfuric acid, ammonium sulfate, and the graphite material in a preset ratio; and maintaining the mixture of concentrated sulfuric acid, ammonium sulfate, and the graphite material at a preset temperature for a preset time.
[0047] In some embodiments of the present application, the preset temperature ranges from 50°C to 70°C.
[0048] In some embodiments of the present application, the preset duration ranges from 1 hour to 3 hours.
[0049] In some embodiments of the present application, the mass ratio of the ammonium sulfate to the graphite material is in the range of 1:(0.33-0.5).
[0050] In some embodiments of the present application, when the pickled graphite material is subjected to microwave irradiation, the frequency of the microwave irradiation ranges from 1.85 GHz to 3.15 GHz.
[0051] In some embodiments of the present application, the duration of microwave irradiation on the pickled graphite material ranges from 8 minutes to 25 minutes.
[0052] The above scheme is adopted to remove impurities in graphite by reacting microcrystalline graphite with an acidic solvent composed of concentrated sulfuric acid and ammonium sulfate in a certain ratio. The impurities mostly coexist with the graphite lattice structure in an embedded manner. The effective removal of impurities can increase the porosity in the graphite, and at the same time enhance the compatibility of graphite with other solvents, which is conducive to increasing the hydrophilicity of graphite. The acidic solvent is composed of concentrated sulfuric acid and ammonium sulfate in a certain ratio. Concentrated sulfuric acid is often used as one of the oxidants in graphite chemical purification. It can not only enter the graphite interlayer to react with the graphite interlayer compound, but also react with graphite to generate sulfuric acid-graphite interlayer compound.
[0053] As a specific solution, as an example, the mass ratio of concentrated sulfuric acid: ammonium sulfate: graphite can be 20:2:1, wherein concentrated sulfuric acid is added to ensure the stirring of graphite powder, and ammonium sulfate is used to control the degree of oxidation reaction. This treatment causes the graphite to form a porous structure, effectively increases the specific surface area of the graphite, opens the wetting channel, and provides more contact area.
[0054] This porous structure is conducive to the contact between the subsequent coating agent and graphite. The heating temperature is controlled at 60°C, and microwave irradiation heating can be used as an example in this application.
[0055] Ammonium sulfate plays the following roles in this scheme: as an oxidant, it can play the role of an oxidant in the chemical purification process and participate in the purification process, promoting the oxidation of graphite and impurities; ammonium sulfate can react with graphite to generate gas, which helps graphite form porous channels, helps to improve the wetting effect of subsequent coating agents, and achieves the beneficial effects of opening channels to increase specific surface area and reducing specific surface area after coating; due to the addition of concentrated sulfuric acid, it has strong oxidizing properties, and the addition of an appropriate amount of ammonium sulfate has the effect of adjusting the degree of oxidation, so that impurities can be removed while avoiding excessive oxidation of graphite. Acidic solvents are used to react with impurities in the graphite structure, and heat pretreatment is applied at the same time, so that the acidic solvent molecules entering the graphite flakes are quickly vaporized or decomposed into gas to generate instantaneous high pressure to increase the distance between graphite layers.
[0056] The solvent composed of concentrated sulfuric acid and ammonium sulfate has a significant impact on the purification effect and the beneficial effects of the subsequent coating process due to different ratios during the graphite purification process.
[0057] In order to avoid overoxidation of graphite crystals, the mass ratio of concentrated sulfuric acid: ammonium sulfate: graphite is limited to 20:2:1, the reaction temperature is controlled at 60 degrees Celsius, and the reaction time is limited to 2 hours.
[0058] It is understandable that microwave irradiation heating can quickly vaporize or decompose acidic solvent molecules into gas, generate instantaneous high pressure, and increase the distance between graphite layers. Principle of microwave irradiation heating: Microwaves are electromagnetic waves with a wavelength range of approximately 1 mm to 1 m and a frequency of 300 MHz to 300 GHz. When microwaves pass through a substance, their rapidly changing electromagnetic field causes the polar molecules in the substance to rotate or vibrate rapidly, thereby generating frictional heat and causing the temperature of the substance to rise. This microwave irradiation heating uses a frequency of 2.45 GHz and lasts for 10 minutes to ensure that the polar molecules effectively absorb the irradiated microwave energy.
[0059] As a specific solution, the frequency of the microwave irradiation ranges from 1.85 GHz to 3.15 GHz.
[0060] After washing with water to remove the acidic solvent, liquid phase asphalt coating is performed, so that the graphite interlayers and the end faces of the graphite structure are coated with asphalt. After washing with water to remove the acidic solvent, liquid phase asphalt coating is performed, so that the graphite interlayers and the end faces of the graphite structure are coated with asphalt, and high temperature graphitization is performed.
[0061] The coating adopts the method of vacuum impregnation of graphite with liquid asphalt. Due to the internal channels formed by the acidic solvent on the graphite in the previous impurity removal process, the liquid asphalt smoothly infiltrates the internal pores in this process.
[0062] In this specific scheme, the solid-liquid ratio of the slurry is required to be 1:20 to ensure that the liquid asphalt coated slurry can be stirred. The stirring time is set to 1 hour to ensure that the asphalt and graphite are fully mixed. At the same time, it should be noted that different stirring times may affect the coating effect of the asphalt and the agglomeration of the graphite particles.
[0063] The present application is mainly based on the following mechanism: due to the infiltration of acidic substances, the space originally occupied by impurities in graphite is released due to the acidic substances dissolving it. During the heating process, the acidic substances or washing solutions that have not been removed are subjected to microwave irradiation and are rapidly heated, which helps to release gas molecules. These gas molecules can destroy the van der Waals force between carbon layers, thereby promoting the expansion of graphite aromatic sheets. In addition, microwave irradiation is more uniform in energy conduction in the container than other heating methods, and can make graphite be subjected to a uniform induced electric field, which can ionize air and form plasma. This plasma can heat the graphite surface to an extremely high temperature (about 1400K) in a very short time. This rapid heating process can also promote the rapid decomposition or gasification of compounds between graphite layers, produce a large amount of gas, and cause graphite to peel off along the C axis direction; due to the removal of impurities and the destruction of the layered structure, the graphite after this microwave irradiation often produces a porous structure, which is related to the number of water washings, acid residue (pH value), microwave action time, and the particle size of graphite.
[0064] More specifically, the graphitization heating curve and temperature setting, the graphitization temperature usually needs to be above 2500℃. This test adopts a slow heating method at 10℃ / minute, steadily heating to 1200℃, keeping warm for 1 hour, and quickly raising the temperature to 2700 degrees Celsius at a heating rate of 50℃ / minute, and keeping warm for 2 hours to ensure uniform heating and graphitization of the material. For the graphitization atmosphere, the high-temperature graphitization operation is carried out under the protection of inert gas argon.
[0065] At high temperatures, disordered graphite sheets grow in different directions and eventually interweave with each other. The graphite planes are interlaced in various forms, and the grain boundaries are interwoven to further increase the stability of the structure, ultimately forming a dense and stable high-purity graphite material. Under such a structure, the internal layers are interwoven, and the powder features of the external thorny ball structure enable it to resist the volume effect during the migration of lithium ions between graphite crystal layers due to the stable support structure, thus having a long cycle performance in electrochemical tests. The negative electrode material is obtained after coating and carbonization with modified asphalt.
[0066] The technical solution of the present application can significantly improve the lithium storage capacity and electrochemical performance of graphite materials through the preparation of carbon matrix and its high-temperature graphitization treatment method, while avoiding the problems of structural collapse and sharp reduction in cycle life.
[0067] This application first increases the discreteness of the graphite structure, and then uses amorphous carbon as a supplementary source of graphitized carbon material through impregnation and coating. The graphite sheet structure is interlaced and nested to form a stable grain structure by utilizing the evolutionary trend of graphitization on the extension and growth of graphite sheets. This has a significant beneficial effect on resisting the volume effect in the subsequent electrochemical cycle process, and is conducive to extending the charge and discharge cycle performance of the product.
[0068] The following is a detailed description of the present invention with reference to the examples, and illustrates the benefits of the present invention through comparative examples.
[0069] Example 1
[0070] (1) This embodiment uses microcrystalline graphite flotation concentrate with a carbon content of 85% as the substrate. First, the microcrystalline graphite flotation concentrate is crushed and ground to obtain microcrystalline graphite with different particle size ranges. The specific particle size range is shown in Table 1.
[0071] (2) The above-mentioned microcrystalline graphite of different particle size ranges is reacted with an acidic solvent composed of concentrated sulfuric acid and ammonium sulfate in a certain ratio to remove impurities in the graphite. In this embodiment, the mass ratio of concentrated sulfuric acid: ammonium sulfate: graphite is 20:2:1. This treatment is intended to increase the porosity in the graphite, enhance the compatibility of graphite with other solvents, and improve hydrophilicity. The reaction conditions are a heating temperature of 60°C, microwave irradiation heating, and a reaction time limit of 2 hours.
[0072] (3) Microwave irradiation heating is adopted, the microwave irradiation frequency is 3.15 GHz, and the action time is 10 minutes. The principle of microwave irradiation heating is to use the rapidly changing electromagnetic field of microwaves to make the polar molecules in the material rotate or vibrate rapidly, generate friction heat, and thus increase the temperature of the material. This step helps the acidic solvent molecules to quickly vaporize or decompose into gas, generate instantaneous high pressure, and increase the distance between graphite layers.
[0073] (4) After washing to remove the acidic solvent, liquid asphalt coating is performed. This embodiment requires a slurry solid-liquid ratio of 1:20 and a stirring time of 1 hour to ensure that the asphalt and graphite are fully mixed and uniform. The vacuum pressure impregnation equipment is used to allow the liquid asphalt to enter the graphite grains along the void channels exposed after impurities are removed, so that the liquid asphalt fills the void channels between the graphite layers and the end faces of the graphite structure and in the graphite, preparing for subsequent high-temperature graphitization.
[0074] (5) The graphitization process adopts a slow heating method, heating to 1200℃ at a rate of 10℃ / min, keeping it warm for 1 hour, and then rapidly heating to 2700℃ at a rate of 50℃ / min, and keeping it warm for 2 hours. Graphitization is carried out under the protection of inert gas argon to ensure uniform heating and graphitization of the material. After graphitization, the graphite sheets grow in different directions and interweave with each other to form a high-purity graphite material with a dense and stable structure.
[0075] (6) The negative electrode material is obtained by coating and carbonizing with modified asphalt. The negative electrode material has the characteristics of internal interlayer interweaving and external thorn ball structure. In the process of lithium ion migration between graphite crystal layers, the support structure is stable and has the ability to resist the volume effect, so that it has a long cycle performance in electrochemical testing.
[0076] Example 2
[0077] The difference from Example 1 lies in the selection of microcrystalline graphite and the selection of microwave irradiation frequency, as shown in Table 1 for details.
[0078] Example 3
[0079] The difference from Example 1 lies in the selection of microcrystalline graphite and the selection of microwave irradiation frequency, as shown in Table 1 for details.
[0080] Example 4
[0081] The difference from Example 1 lies in the selection of microcrystalline graphite and the selection of microwave irradiation frequency, as shown in Table 1 for details.
[0082] Example 5
[0083] The difference from Example 1 lies in the selection of microcrystalline graphite and the selection of microwave irradiation frequency, as shown in Table 1 for details.
[0084] Example 6
[0085] The difference from Example 1 lies in the selection of microcrystalline graphite and the selection of microwave irradiation frequency, as shown in Table 1 for details.
[0086] The negative electrode materials obtained in the above-mentioned embodiments were tested to obtain performance data such as La value and cycle retention rate.
[0087] Test Method
[0088] The samples were made into 554065 soft pack batteries for testing. The specific preparation and testing methods are as follows:
[0089] 1 The preparation process of soft pack batteries is as follows:
[0090] The overall process is pulping - coating - rolling - cutting - laminating - micro short circuit test - spot welding of the tabs - aluminum plastic sealing - liquid injection - vacuum standing - brewing - hot pressing - acupuncture final sealing
[0091] 2. Pulping
[0092] (1) Raw material ratio
[0093] The positive electrode solid content is 45-55%, and the negative electrode solid content is 40-50%. The solid content refers to the ratio of the mass of the dry slurry to the mass of the wet slurry before drying.
[0094] positive electrode LFP PVDF SP percentage 93% 3% 4%
[0095] negative electrode graphite CMC SP SBR percentage 93.2% 1.8% 2.5% 2.5%
[0096] (2) Stirring and dispersing
[0097] First, mix NMP and PVDF and stir. PVDF can be added in small amounts and multiple times to facilitate uniform stirring. Add LFP powder and then add NMP to stir and disperse. The mixer cannot stir continuously and must be allowed to cool for a certain period of time. Then, vacuum and degas. Complete the stirring.
[0098] The stirring effect mainly depends on the test of the slurry fineness and viscosity. Generally, the fineness of the positive electrode is 5-10μm, and the fineness of the negative electrode is 15-20μm. When measuring the fineness, the scraper speed should not be too fast. The centrifugal mixing tank should not be filled with too much material, occupying about 1 / 3 of the volume.
[0099] 3. Coating
[0100] The prepared positive and negative electrode slurries are coated on aluminum foil and copper foil respectively by manual or automatic methods. During coating, attention should be paid to the matching of the surface density and capacity of the positive and negative electrodes. In this preparation, the n / p ratio (negative electrode capacity per unit area / positive electrode capacity per unit area) is always used at 1.2.
[0101] 4. Roller pressing
[0102] The roller thickness is achieved by adjusting the gap and pressure, and the compaction density of the negative electrode is 1.52.3g / cm 3 The positive electrode compaction density is 2.3g / cm 3 .
[0103] 5. Cutting
[0104] The size of the negative electrode is 53mm, the positive electrode is 50mm, and the outer shell is 60mm. After the positive and negative electrodes are cut, they need to be powdered to remove the loosely adhered powder to avoid puncturing the diaphragm.
[0105] 6. Lamination
[0106] There are 21 negative electrodes and 20 positive electrodes. When stacking, be careful not to let the positive and negative electrodes touch each other to avoid short circuit. This test uses automatic stacking, and after stacking, use tape to fix the sheets (two methods of sticking tape).
[0107] 7. Micro short circuit test
[0108] High voltage (200V) and pressure (1 MPa) are applied. If the current fluctuates slightly and then quickly drops to zero, it can be judged that there is a micro short circuit; if the current is large, it can be judged that there is no micro short circuit. After lamination, a micro short circuit test is performed at each step, and after screening, the next process is carried out.
[0109] 8. Spot welding of lugs
[0110] First weld the stacked tabs, then spot weld the tabs together with the positive and negative tabs. After welding, apply tape to the welding points to prevent falling off and short circuit.
[0111] 9. Aluminum-plastic sealing
[0112] The aluminum-plastic film consists of three layers, the inner layer is PP film, the middle layer aluminum film plays a plastic role, and the outermost layer is nylon layer; when the aluminum-plastic film is molded, it is placed according to the principle of the mold so that the innermost layer forms a molded shape; after the shape is molded, the battery cell is put in, first top seal and then side seal, after top seal, pinch it with your hands, and when side seal, try to seal it close to the side of the battery cell. After plastic sealing, use black tape to seal the long pole ear to avoid short circuit caused by pole ear contact. The film thickness is 0.6-0.8 mm smaller than the thickness of the battery cell.
[0113] Baking: evaporate excess water (baking temperature: 80°C), vacuum: -0.1MPa, time: no less than 12h.
[0114] 10. Injection
[0115] Vacuum injection (-85 kPa). The injection amount is based on the empirical value. The capacity of a soft-pack battery is 1 ampere-hour, the ternary positive electrode capacity of 1 ampere-hour requires 4.0 grams, and lithium iron phosphate requires 4.5g electrolyte.
[0116] After standing in vacuum (pressure -95 kPa, independent of temperature) for 2 minutes, the electrolyte is dripped into the soft-pack battery and vacuum pre-sealed (-95 kPa, temperature 180°C).
[0117] 11. Battery formation (positive electrode is lithium iron phosphate)
[0118] (1) Formation: Allow the electrolyte to fully penetrate the electrode material and the diaphragm. Set the temperature to 45°C and place at normal pressure for ≥ 24 hours.
[0119] (2) Charge and discharge test
[0120] Let stand for 5 minutes - charge with a small constant current of 0.05C to 2.6V, and 0.1C to 3.2V - let stand for 5 minutes.
[0121] 12. Battery aging
[0122] Place the sealed battery in a forced air oven at 45°C for more than 12 hours, test the battery self-discharge, and stabilize the SEI film.
[0123] 13. Battery final sealing
[0124] The formed battery is punctured, vacuumed and sealed again.
[0125] 14. Performance Testing
[0126] The test is based on the "Lithium Iron Phosphate Electrochemical Performance Test Discharge Platform Capacity Ratio and Cycle Life Test Method", which is managed by TC243 (National Technical Committee for Nonferrous Metals Standardization) and implemented by TC243SC4 (National Technical Committee for Nonferrous Metals Standardization Powder Metallurgy Branch), and the competent department is the China Nonferrous Metals Industry Association. The main drafting units are Xi'an Taijin Industrial Electrochemical Technology Co., Ltd. and Northwest Nonferrous Metals Research Institute.
[0127] Table 1
[0128]
[0129] As shown in Table 1, under microwave irradiation with a frequency of 1.85 GHz to 3.15 GHz, the acidic solvent molecules remaining after pickling are rapidly vaporized or decomposed into gas, generating instantaneous high pressure, and the asphaltene component is fully infiltrated. In the subsequent graphitization, the graphite sheets are further enlarged, which is conducive to the growth of graphite sheets and interlacing with each other, forming a more stable interlaced structure, which is helpful in the cycle process, offsetting the volume expansion caused by lithium ion insertion and extraction, reducing the risk of graphene sheets escaping from the graphite body, and improving its ability to store conductive materials (such as lithium storage). The stability of the graphite sheet structure further improves the cycle attenuation of the battery. As shown in Table 1, although a higher microwave irradiation frequency can obtain better performance (such as La value or retention rate), a higher frequency represents a higher energy loss, and a higher energy means that other beneficial microstructures in the graphite negative electrode material may be destroyed. As shown in Table 1, when the microwave irradiation frequency exceeds 3 GHz, the retention rate is close to a higher standard. Therefore, in consideration of balance, the microwave irradiation frequency is not the higher the better.
[0130] The technical solutions provided by the embodiments of the present application are introduced in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method of the present application and its core idea. At the same time, for technical personnel in this field, according to the idea of the present application, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.
Claims
1. A method for preparing a graphite negative electrode material, characterized in that: The preparation method of the graphite negative electrode material comprises: The pickled graphite material is subjected to microwave irradiation; Carrying out water washing treatment on the graphite material after microwave irradiation; The graphite material after water washing is graphitized.
2. The preparation method according to claim 1, characterized in that: in, The raw material of the graphite material is microcrystalline graphite.
3. The preparation method according to claim 2, characterized in that: in, The mass percentage of the carbon content of the microcrystalline graphite ranges from 80% to 95%.
4. The preparation method according to claim 2, characterized in that: in, The median particle size of the microcrystalline graphite ranges from 8 μm to 22 μm.
5. The preparation method according to claim 1, characterized in that: The method for preparing the graphite negative electrode material also includes: Coating the graphite material after graphitization to form the graphite negative electrode material; And / or, pickling the graphite material, wherein the pickling of the graphite material comprises: mixing concentrated sulfuric acid, ammonium sulfate and the graphite material according to a preset ratio; A mixture of concentrated sulfuric acid, ammonium sulfate and graphite material is maintained at a preset temperature for a preset period of time.
6. The preparation method according to claim 5, characterized in that: in, The preset temperature ranges from 50°C to 70°C; And / or, the preset duration ranges from 1h to 3h; And / or, the mass ratio of the ammonium sulfate to the graphite material is in the range of 1:(0.33-0.5).
7. The preparation method according to any one of claims 1 to 6, characterized in that: in, When the pickled graphite material is subjected to microwave irradiation, the frequency of the microwave irradiation ranges from 1.85 GHz to 3.15 GHz.
8. The preparation method according to any one of claims 1 to 6, characterized in that: in, The duration of microwave irradiation on the pickled graphite material ranges from 8 minutes to 25 minutes.
9. A graphite negative electrode material, characterized in that: The graphite negative electrode material is prepared by the preparation method according to any one of claims 1 to 8.
10. A secondary battery, characterized in that: A negative electrode comprising the graphite negative electrode material according to claim 9.